The Moderating Role of Dividend Policy in Optimizing the Effect of Profitability and Investment Decisions on Corporate Value Creation - Indriani, Anisa Putri; Annis, Barlia (The Future of Education Journal, 2026)
This study aims to examine the effects of profitability and investment decisions on firm value, with dividend policy serving as a moderating variable. Profitability in this study is measured using Return on Assets (ROA), investment decisions are measured using Total Assets Growth (TAG), dividend policy is formulated through the Dividend Payout Ratio (DPR), and firm value is measured based on Price to Book Value (PBV). This research employs a quantitative approach, with samples selected using purposive sampling techniques. A total of 76 samples were obtained from 19 LQ45 companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. Using multiple linear regression analysis, the results indicate that firm value is positively influenced by profitability. Meanwhile, investment decisions have no significant effect on firm value. Dividend policy is able to moderate the relationship between profitability and firm value. However, dividend policy is unable to moderate the relationship between investment decisions and firm value.